2003
DOI: 10.1086/379738
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus–Induced Apoptosis of Human Hepatocytes via CXCR4

Abstract: Human immunodeficiency virus (HIV) infection is commonly associated with liver dysfunction. The X4 HIV glycoprotein 120 envelope (env) induces apoptosis in T cells and neurons via the HIV coreceptor CXCR4. Therefore, we investigated whether hepatocyte death could result from the HIV env signaling through CXCR4 on the hepatocyte. We demonstrated that hepatocytes in humans express CXCR4 on the cell surface. Furthermore, we established that the X4 HIV env and the entire HIV virion signal hepatocyte apoptosis thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 15 publications
4
98
0
1
Order By: Relevance
“…primarily CXCR4 or CCR5), which are considered as the main surface proteins allowing membrane fusion. While it is unlikely that CD4 is expressed in hepatocytes because this molecule is found primarily on immune cells, some authors have reported controversial results about the expression of the coreceptors on human hepatoma cell lines (Banerjee et al, 1992;Cao et al, 1990;Iser et al, 2010;Vlahakis et al, 2003). To assess whether the weak HIV-1 susceptibility displayed by Huh7.5 cells could be explained by the absence of CD4 and/or co-receptor on the plasma membrane, flow cytometry analysis was performed.…”
Section: Inefficient Fusion Is Due To a Lack Of Cell Surface Receptorsmentioning
confidence: 99%
“…primarily CXCR4 or CCR5), which are considered as the main surface proteins allowing membrane fusion. While it is unlikely that CD4 is expressed in hepatocytes because this molecule is found primarily on immune cells, some authors have reported controversial results about the expression of the coreceptors on human hepatoma cell lines (Banerjee et al, 1992;Cao et al, 1990;Iser et al, 2010;Vlahakis et al, 2003). To assess whether the weak HIV-1 susceptibility displayed by Huh7.5 cells could be explained by the absence of CD4 and/or co-receptor on the plasma membrane, flow cytometry analysis was performed.…”
Section: Inefficient Fusion Is Due To a Lack Of Cell Surface Receptorsmentioning
confidence: 99%
“…31 These potent cytotoxic effects have been implicated in the HIV-1-induced lymphodepletion, HIV-associated dementia (also called HIV encephalitis or neuro-AIDS), AIDS-cardiomyopathy, as well as AIDS associated nephropathy and hepatopathy.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%
“…First, Env ligation of CD4 can sensitize cells to Fas-mediated death (7,8) through a CD4 signaling-dependent process (9,10). Second, ligation of the chemokine receptor (CXCR4 for lymphocytes and CCR5 for monocytes) can induce apoptosis through either a G i␣ -dependent or independent mechanism depending on cell type (11,12). Third, a temporary and incomplete Env CD4/chemokine receptor-mediated hemifusion can occur and induce death through a caspase-independent pathway that involves a loss of mitochondrial transmembrane potential (13,14).…”
Section: H Uman Immunodeficiency Virus-1 Infection Causes the Inevitamentioning
confidence: 99%